Mensuração de níveis de integração entre membros de uma cadeia de suprimentos: proposta de uma escala para avaliar os relacionamentos a montante - Arantes, Fernanda Paes (2014)
The integration is highlighted in the literature as essential characteristic to the supply chain management (SCM), once aligned to strategic decisions, it produces more effective results, increases sensitivity to customer needs, decreases the response time to market changes and other factors that lead to increased performance of the chain as a whole. However, although the importance of integration is widely recognized, there is still much disagreement regarding its definition and therefore, difficult to measure the level of integration among members of a supply chain, making it difficult to evaluate the current chain state as well as the possibility of improvement. Thus, this research aims at developing a scale to measure the level of integration among members of a supply chain, focusing on upstream relationships, using the Item Response Theory (IRT). For this purpose we sought to identify the characteristics of integration through situations that indicate their existence by the following steps: 1) development of a scale to measure the level of integration with among members upstream the chain, based on the characteristics of integration identified in the literature review: confidence, information sharing, partnership, cooperation, coordination and collaboration, 2) preparation of items with situations that indicate the existence of these aspects in the relationship among members, building a scale to measure the level of integration between company and supplier, 3) measuring the level of integration of the companies participating in the research. The definition of the level of integration indicated by each item allowed the confirmation of the existence of a cumulative relationship among features of integration, based on the confidence that enables the sharing of information, followed by partnership and cooperation, coordination and collaboration among members.